Kryteria oceny polityki reasekuracyjnej zakładów ubezpieczeń - Poprawska, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
An insurance policy is a very important part of the financial management of an insurance company. The policy is should be evaluated by insurance companies, insurance control, and rating agencies. In the paper the mail elements of the evaluation the reinsurance policy, that are applied by the insurance control, and additional, that are applied by rating agencies. The criteria are applied to evaluate passive reinsurance in non-life insurance companies.Then the results of calculation several reinsurance policy ratios are presented. The analysis are done for the year 2003 for the whole market and selected insurance companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 139-145